Desenvolvimento de aplicativo baseado no método de Duval para análise de gases em transformadores - Barbosa, Thales Mendes (2016)
This work proposes the development of an application on the analysis of gases dissolved in mineral transformer oil, of all classes of voltage and power, the Duval Triangle method. Through simulations in the application, we obtain results of incipient faults in transformers, as well as pie charts of percentages of gases analyzed by the method. They will be made comparisons of application simulations with the results of fault diagnosis, with the intention to verify its performance. In the final considerations suggestions for improvements for future projects will be presented, with respect to diagnostics to obtain fault in the transformer insulation system.